Skills trained by coaches of Canadian male volleyball teams: A comparison with longterm athlete development guidelines - Chevrier, J.; Roy, M.; Turcotte, S.; Culver, D. M.; Cybulski, S.; Renshaw, I.; Till, K. (International Journal of Sports Science & Coaching, 2016)
Volleyball Canada and Volleyball Quebec developed long-term athlete development models in order to guide volleyball coaches concerned with athlete development. These models propose guidelines about the development of skills. However, it has yet to be determined whether coaches apply long-term athlete development guidelines in their coaching practice. Therefore, the objectives of this study were to describe the amount of time devoted to the various skills trained by four volleyball coaches of different levels and to compare these training skills with the long-term athlete development guidelines. The results of this multiple case study (n = 4) indicated that based on long-term athlete development guidelines, (a) college and university coaches over-trained technical skills; (b) high school coaches and university coaches undertrained individual tactical skills; and (c) high school coaches over-trained team tactical skills. Corrective measures that might help coaches apply the long-term athlete development guidelines are changes in the access to training facilities, competition schedules, and coach education programs. ABSTRACT FROM AUTHOR